ECOLOGICAL AND AGROCHEMICAL ASSESSMENT OF SOIL SUITABILITY OF AGRICULTURAL ENTERPRISE FOR ORGANIC PRODUCTS CULTIVATION - Hlovyn, N. M.; Pavliv, O. V. (Scientific Progress & Innovations, 2021)
The article highlights the results of investigating land agro-ecological condition by ecological and agro-chemical indicators of agro-ecosystems in “Zhyva Zemlia Potutory” LLC (organic farming method) in Be-rezhany district of Ternopil region. Organic farming has to be based on the principles of natural environ-mental systems and cycles, working, coexisting with them and supporting them. The results are achieved by farm eco-balancing. For example, for plants it is live soil, for animals it is farm ecosystem, for fish and sea organisms – water environment. The Law “On the production and circulation of organic farm products and raw materials” is the basis of Ukrainian legislation governing the “organic” sphere. This Law as if prohib-its the application of fertilizers, pesticides, but admits a number of exceptions. Organic production is one of the priority areas of agricultural development in the world, as it is almost the only one among a wide range of economic methods, which does not have a negative impact on the environment and human health. The ar-ticle describes the statistical generalization of indicators of organic technologies development on the farm and draws conclusions about the relevance of this strategic technological direction for the region. Peculiari-ties of soil indicators on the farm from the position of the determined agrochemical indices as to cultivating organic products have been analyzed. The average indicators of the soil agrochemical properties on the farm in terms of humus content, labile forms of nitrogen, phosphorus and potassium, soil solution acidity have been grouped and determined. Based on the comparison of standard values of soil parameters and ac-tual values of indicators on the farm, the state of soil suitability for introducing organic technologies of agri-cultural products manufacturing has been determined. This allowed find favorable and unfavorable factors for the transition to organic technologies of agrarian production. In view of the above mentioned, we think that the restoration of our most fertile and valuable black soils is not a myth, but a reality, which must be implemented today.